Advances in applied mechanics and materials : selected, peer reviewed papers from the International Conference on Mechanical Engineering (ICOME 2013), September 19-21, 2013, Mataram, Lombok, Indonesia - Pramujati, Bambang (Applied mechanics and materials, 2014)
Collection of selected, peer reviewed papers from the International Conference on Mechanical Engineering (ICOME 2013), September 19-21, 2013, Mataram, Lombok, Indonesia. The 130 papers are grouped as follows: Chapter 1: Energy Conversion; Chapter 2: Mechanical Design; Chapter 3: Manufacturing Processes and Technologies; Chapter 4: Material Science and Engineering Temporary description, more details to follow.